2015
DOI: 10.1021/acs.biochem.5b00013
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Aminodeoxychorismate Synthase into Anthranilate Synthase with Janus Mutations: Mechanism of Pyruvate Elimination Catalyzed by Chorismate Enzymes

Abstract: The central importance of chorismate enzymes in bacteria, fungi, parasites, and plants combined with their absence in mammals makes them attractive targets for antimicrobials and herbicides. Two of these enzymes, anthranilate synthase (AS) and aminodeoxychorismate synthase (ADCS), are structurally and mechanistically similar. The first catalytic step, amination at C2, is common between them, but AS additionally catalyzes pyruvate elimination, aromatizing the aminated intermediate to anthranilate. Despite prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…Both reactions occur in the same active site. The cleavage reaction has been hypothesized to be a pericyclic reaction [64, 65]; however, there is a recent resurgence for the idea that the elimination reaction is also general acid-general base catalyzed [66]. …”
Section: Generation Of Secondary Metabolites For Incorporation Intmentioning
confidence: 99%
“…Both reactions occur in the same active site. The cleavage reaction has been hypothesized to be a pericyclic reaction [64, 65]; however, there is a recent resurgence for the idea that the elimination reaction is also general acid-general base catalyzed [66]. …”
Section: Generation Of Secondary Metabolites For Incorporation Intmentioning
confidence: 99%
“…[12] Therefore,the most plausible explanation for the lack of pyruvate-elimination activity in most ICS-active stAS variants is perturbations in the IC ring conformation caused by the introduced mutations.…”
mentioning
confidence: 99%
“…It is worth noting that only four of the ICS-active stAS variants also formed SA, which involves the elimination of pyruvate from IC.T his finding seems counterintuitive at first because the generic product of stAS is AA, which has,l ike SA, undergone elimination of pyruvate.H owever,i t was recently shown that the elimination of pyruvate from chorismate-derived reaction intermediates in MST enzymes is controlled by the conformation of the chorismate ring structure. [12] Therefore,the most plausible explanation for the lack of pyruvate-elimination activity in most ICS-active stAS variants is perturbations in the IC ring conformation caused by the introduced mutations.…”
mentioning
confidence: 99%
“…Although the detailed polymerization of alanine, anthranilic acid and tryptophan is unclear, the early steps of CHA biosynthetic pathway were verified as involving the shikimate pathway in our previous work [16]. There are some key sites for control in the shikimate pathway, such as 3-deoxy-arabino-heptulosonate-7-phosphate synthase (DAHP, dahp), chorismate synthase (cs) and anthranilate synthase (trpC) [17][18][19]. In addition, laeA, a global regulator, plays an important regulation role in the biosynthesis of secondary metabolites, such as the effect of deletion/overexpression of laeA in Aspergillus app.…”
Section: Introductionmentioning
confidence: 90%